Pregled zgodovine slovenske skupnosti v Elyju, Minnesota - Klemenčič, Matjaž; Šeruga, Tadej (University of Maribor Press, 2019)
The Survey of the History of the Slovene American community in Ely, Minnesota. The book presents the history of Ely, Minnesota, a mining town which has since the 1890s till the present day developed into a tourist destination. The role of Slovene Americans, who represented a relative majority in the town, is of particular importance to the authors, who also deal with the environ‑ mental concerns pertinent to northern Minnesota and their impact on the economic history of the region. A special chapter is devoted to the numeri‑ cal strength and the geographical locations of Slovene Americans living in the U.S., Minnesota and Ely. The statistical data on which the authors base their findings are taken from the U.S. censuses for the period from1910 until 1980. Furthermore, they describe the history of St. Paul (Arch)dio‑ cese, and of the Duluth Diocese as well as the role that Slovene American Catholic priests played in their development. Within this framework they then describe the history of St. Anthony de Padua Parish. The final chapter is devoted to Slovene Americans who have succeeded in politics both on a local level as mayors (Brozich and Grahek) and nationally (Congressmen Blatnik and Oberstar; Senator Amy Klobuchar) as well as in cultural life and in journalism (Kuralt and Jim Klobuchar).